2003
DOI: 10.1074/jbc.m302841200
|View full text |Cite
|
Sign up to set email alerts
|

Kennedy's Disease

Abstract: X-linked spinal and bulbar muscular atrophy is a degenerative disease affecting motor neurons that is caused by polyglutamine (polyQ) expansion within the androgen receptor (AR). The polyQ-expanded form of AR is cytotoxic to cells, and proteolytic cleavage enhances cell death. The intracellular signaling pathways activated and/or required for cell death induced by the expanded form of AR (AR112) are unknown. We found that AR regulates mitogen-activated protein kinase (MAP kinase) pathways and, therefore, hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Other work on Htt as well as the androgen receptor has shown that phosphorylation at more distal sites can modulate cleavage. In a related polyglutamine disease, Kennedy disease, we have shown that the phosphorylation of androgen receptor modulates proteolysis and toxicity (38). Our studies found that phosphorylation at Ser-514 of the androgen receptor, a site distal to the caspase cleavage site at amino acid 154, enhanced cellular toxicity and the production of cytotoxic fragments.…”
Section: Discussionmentioning
confidence: 66%
“…Other work on Htt as well as the androgen receptor has shown that phosphorylation at more distal sites can modulate cleavage. In a related polyglutamine disease, Kennedy disease, we have shown that the phosphorylation of androgen receptor modulates proteolysis and toxicity (38). Our studies found that phosphorylation at Ser-514 of the androgen receptor, a site distal to the caspase cleavage site at amino acid 154, enhanced cellular toxicity and the production of cytotoxic fragments.…”
Section: Discussionmentioning
confidence: 66%
“…Alternatively, SUMO modification of the SC motifs in AR may prevent proteolytic steps that are thought to be involved in the generation of toxic polyglutamine-containing fragments (77,78). In this regard, SUMOylation could antagonize the phosphorylationdependent caspase 3 cleavage of AR, which is closely associated with neuronal toxicity (79).…”
Section: Discussionmentioning
confidence: 99%
“…For example, testosterone activation of the androgen receptor increases the expression of cytoskeleton proteins, such as tubulin (63) and neuritin (64), which are important for neurite outgrowth and neuronal differentiation. Mutations of the androgen receptor that cause aggregation of polyglutamine-expanded protein induce cytotoxicity with normal levels of testosterone (65,66), a primary cause of Kennedy syndrome (67). The effect of high testosterone concentration on cell function in these altered cells is not known.…”
Section: Discussionmentioning
confidence: 99%